Vocaloid : A Modern Vocal Synthesizer for Creating Human-Like Vocal - Stephan Adiatma (IC-ITECHS, 2020)
Nowadays, digital media keeps growing to its greater extent along with electronics advancement. It brings impact to the music industries. Varieties of unique and genuinely different genres have been developed. This development has created a software that imitates human voice, called Vocaloid. Vocaloid is a program which helps a composer or a musician in composing and making music with vocal sound by vocalizing a lyric that has been written. Currently, there are many composers or musicians who have already used this software for remaking a cover music or making an original music. Hatsune Miku is the most popular vocaloid used currently. Furthermore, it can be found in many YouTube channels that use Hatsune Miku in their videos. Their videos have reached millions of views. It is expected that the vocaloid software can help many composers or musicians for making many creative music.